Acral perineurioma: a case report of a rare neoplasm successfully treated with autologous skin graft reconstructive surgery - Elena Pierobon; Chiara Cortelazzi; Michele Maria Dominici; Claudio Feliciani; Sergio Di Nuzzo (PAGEPress Publications, 2021)
Soft tissues perineurioma is a rare nerve sheath tumor that affects most of all the subcutaneous tissue. Even if it could present as a large mass, it is a benign neoplasm for whom a complete surgical excision represents the gold standard treatment. Considering that it usually affects acral sites of young people, can be challenging to perform a reconstructive surgery that allows a full functional recovery. We report the case of a woman in her 20s presenting a perineurioma of the sole of the foot, a nodule of about 2 cm of diameter that compromised the support of the foot on the ground. We performed a radical surgical excision with no recurrence after 3 years of follow up and we obtained a full functional recovery thanks to an autologous full-thickness skin graft.